Economic assessment of eltrombopag in the treatment of thrombocytopenia. (August 2015) - Romano, Federica; Ruggeri, Matteo; Coretti, Silvia; Giannini, Edoardo Giovanni; Sacchini, Dario; Annichiarico, Brigida Eleonora; Marchetti, Marco; Rodeghiero, Francesco; Lidonnici, Dario
<x xml:space="preserve">Abstract</x> Objective: This study assesses the cost–effectiveness of eltrombopag in the treatment of hepatitis C virus (HCV)-related thrombocytopenia. Methods: A Markov model was constructed on the basis of the clinical trials ENABLE 1 and ENABLE 2. Three alternatives were considered: scenario 1; treatment with eltrombopag in both the enabling phase and during antiviral therapy, as in the ENABLE trial design; scenario 2; no eltrombopag treatment and no antiviral therapy; scenario 3; no eltrombopag treatment and subsequent administration of a reduced dose of peg-IFN. Results: Base case results demonstrate that scenario 1 is associated with a cost per QALY of €30, 020.94 in comparison with scenario 2. The incremental cost–effectiveness ratio reaches a value of €32, 752.44 per QALY when scenario 1 is compared with scenario 3. Conclusion: The use of eltrombopag in HCV patients with thrombocytopenia is cost-effective as it leads to a reduction in disease progression and thus a drop in the number of patients with advanced liver disease.